ANALISIS AKUNTABILITAS, TRANSPARANSI, DAN PERTANGGUNGJAWABAN PADA PENERIMAAN ZAKAT DALAM MENGELOLA LAPORAN KEUANGAN (PADA BAZNAS KOTA MEDAN) - Siregar, Fifi Hayrani; Harahap, Ardhansyah Putra (Worksheet : Jurnal Akuntansi, 2025)
The aim of this research is to determine accountability, transparency and responsibility for zakat receipts in managing financial reports. This research applies a descriptive qualitative approach, describing and explaining qualitatively with explanatory sentences the Accountability, Transparency and Accountability report data on Zakat Income Levels in the management of Financial Reports at BAZNAS Medan City. The subject of this research is Baznas Medan City. The objects of this research are financial reports, Medan City Baznas zakat fund management reports and the Deputy Chair of Medan City Baznas, Medan City Baznas Financial Staff. The results of this research are that Accountability for Zakat Receipts in Managing Financial Reports: optimal management of zakat funds is able to influence public trust in providing zakat funds to zakat institutions. Transparency in Zakat Receipts in Managing Financial Reports: transparent financial reports have a very important role in building muzakki's trust in BAZNAS Medan City. Financial report transparency refers to the openness and clarity of information presented in the Medan City BAZNAS financial reports. Accountability for Zakat Receipts in Managing Financial Reports: Accountability is very important in managing zakat funds. Accountability for optimal management of zakat funds can influence public trust in providing zakat funds to zakat institutions.